Using solvents for dissolving guttapercha: A systematic review - Z. S. Khabadze; D. A. Nazarova; F. R. Ismailov; A. P. Kotelnikova; E. S. Shilyaeva (LLC "Endo Press", 2022)
Aim. To assess systematically the available scientific evidence about the efficiency and the adverse effects of different solvents dissolving guttapercha.Materials and methods. The study of publications was produced in the electronic databases such as Google Scholar, PubMed during a systematic review of the literature. Included articles contain information about using solvents during endodontic retreatment and their effectiveness and side effects. The publication date criterion was selected from January 2006 to January 2021.Results. 66 articles were viewed during the review. After analyzing the literature for inclusion criteria, the total number of publications has become 13.Conclusions. According to literature data, the frequency of using essential oils (orange oil, grapefruit oil, eucalyptus oil) to dissolve guttapercha in endodontic practice is increasing due to better biocompatibility and lack of cytotoxicity and carcinogenic effects.